The Role of Visionary Leadership in Achieving Strategic Change Through Strategic Improvisation - Kadhum, Ayad Hassan; Muttar, Laith Ali; Khait, Ahmed Abdulhasan (South Asian Journal of Social Sciences and Humanities, 2023)
The research seeks to explain the role of visionary leadership in strategic change through a modern and contemporary theoretical framework for the most prominent presentations of writers and authors on research variables, especially independent variables, visionary leadership and strategic improvisation, which have become the subject of interest’s academics’ , especially in environments with dynamism and rapid change, as well as a practical framework. My analysis of the opinions of a sample of university leaders in private colleges. The aim of the research is to indicate a set of objectives, including: a statement of the relationship between the dimensions of visionary leadership and strategic change, and between improvisation and strategic change and the dimensions of visionary leadership and strategic change through strategic improvisation in private colleges, the research sample, as well as a statement of the effect between these variables, and the research was conducted on a sample It includes 81 university leaders in private colleges in Baghdad, relying on the questionnaire as a basic tool in data collection. The results of the study indicated that the hypotheses of the relationship and influence between all the variables of the study were achieved with varying results, especially with regard to visionary leadership, strategic change, improvisation, and strategic change.